EDUKASI PENYUSUNAN ANGGARAN DAN ANALISIS BREAK EVEN POINT UNTUK PERENCANAAN LABA - Ilmiani, Amalia; Sunarjo, Wenti Ayu; Farha Neha, Madhu (LPPM Univ. Ibn Khaldun Bogor, 2022)
The economic impact of the Covid pandemic is felt by the MSME sector in Pekalongan City. raises new problems, namely a decrease in sales, a decrease in operating profit, a reduction in employees, and obstacles in carrying out their obligations to the bank. The assistance provided by the government to MSMEs affected by the pandemic, if not managed properly, will just run out. The purpose of this community service is to overcome the problems of MSMEs, namely by providing assistance in budgeting and determining selling prices with break even point analysis so as to maximize business profits. Based on the situation analysis, data obtained that MSMEs in Kampoeng Kauman, Pekalongan City did not carry out budget planning, both sales budgets and production budgets and did not analyze break even points in determining the selling price of their products. The selling price fixing method applied by MSMEs in Kampoeng Kauman, Pekalongan City is only based on market prices without performing a break-even analysis. By holding community service, it is concluded that counseling activities about can add insight and knowledge to MSME actors in developing their business. The response from the participants was very enthusiastic during the counseling and training.